THE EFFECTIVENESS OF THE USE OF INNOVATIVE METHODS IN THE PRACTICAL TRAINING OF HUMAN ANATOMY IN THE DIRECTION OF TREATMENT IN MEDICAL INSTITUTIONS - Valijanova Muattar; Turgunova Shakhnoza Tursunovna (Bright Mind Publishing, 2025)
The educational process in medical institutions is an environment that is constantly being updated. Basic subjects, such as human anatomy, provide the knowledge and skills necessary for students to successfully pursue a career in medicine. However, traditional educational methods often do not attract students to the same extent and can reduce their motivation to study. Therefore, the introduction of innovative methods into practical training is important in making the teaching process more efficient and interesting.
Keywords: Medicine, innovative approaches, education, human anatomy, theoretical knowledge, anatomical structures, digital technologies.